School bullying and depression in Chinese primary and secondary school students after the COVID-19: mediating effect of academic anxiety and moderating effect of home-school cooperation - Lan, Ping; Lan, Ling; Zhang, Wei-Ping (Frontiers in Psychology, 2025)
IntroductionThe aim of this study is to explore the relationship between school bullying, depression, academic anxiety, and home-school cooperation among Chinese primary and secondary school students, with a focus on promoting students' mental wellbeing in the post-COVID-19 era.MethodsA survey was conducted among 3,600 Chinese primary and secondary school students using the Depression Scale, School Bullying Scale, Academic Anxiety Scale, and Home-School Cooperation Scale. A total of 3,341 students were selected as research subjects to examine the mediating and moderating mechanisms of academic anxiety and home-school cooperation in the relationship between school bullying and depression. A moderated mediation model was constructed to analyze the impact of school bullying on depression, with academic anxiety as a mediator and home-school cooperation as a moderator.ResultsSchool bullying, depression, and academic anxiety were significantly correlated with home-school cooperation. School bullying was significantly correlated with academic anxiety and depression. School bullying significantly and positively predicted depression. Academic anxiety mediated the relationship between school bullying and depression. Home-school cooperation moderated the relationships between (a) school bullying and academic anxiety, and (b) academic anxiety and depression.DiscussionThe findings indicate that school bullying not only directly increased depression but also indirectly heightened depression through academic anxiety. Home-school cooperation buffered the effects of school bullying on academic anxiety and the effects of academic anxiety on depression.